Nikah Siri dalam Tinjauan Hukum Teoritis dan Sosiologi Hukum Islam Indonesia - Alfin, Aidil; Busyro, Busyro (Fakultas Syariah IAIN Purwokerto, 2017)
The differences of laws in marriage registration have generated argumentative conflicts among the ulama. Some of them agree and the others disagree. Ulama who agree say that proscribing secretly marriage (nikah siri) is in accordance to Islamic law. Even though the regulation about marriage registration has been written in The Indonesian Act No. 1 of 1974 on Marriage and in the Compilation of Islamic Law in Indonesian, the practice of secret marriage is still existed among Indonesian Muslim society. They base their practices on what some of local ShafiiyahUlema say all the time that this kind of marriage is in accordance to shari’ah. It is common to say that Shafi’ischool of law is the largest shari’ahschool of law in Indonesia. In the sociology of Islamic law, most of the scholars in Indonesia who adhere to the Shafi'i school and also most of the Indonesian Muslim community adhere to the same school, may have a significant influence on the constraints of reform of Islamic law related to the registration of marriages in particular and other matters about marriage in general contained in the Law No. 1 of 1974 and the Compilation of Islamic Law in Indonesia.